Clinical and Molecular Spectrum of Glutamate Dehydrogenase Gene Defects in 26 Chinese Congenital Hyperinsulinemia Patients. (16th September 2018) - Su, Chang; Liang, Xue-Jun; Li, Wen-Jing; Wu, Di; Liu, Min; Cao, Bing-Yan; Chen, Jia-Jia; Qin, Miao; Meng, Xi; Gong, Chun-Xiu
Abstract : Objective . To characterize the genotype and phenotype of Chinese patients with congenital hyperinsulinism (CHI) caused by activating mutations in GLUD1, the gene that encodes mitochondrial enzyme glutamate dehydrogenase (GDH). Methods . The clinical data of glutamate dehydrogenase hyperinsulinism (GDH-HI) patients were reviewed, and gene mutations were confirmed by whole exome sequencing (WES) and Sanger DNA sequencing. Results . Twenty-six patients with GDH-HI heterozygous missense mutations were identified from 240 patients diagnosed as congenital hyperinsulinism over past 15 years. The median age at onset was 8 months (range: 1 day of life to 3 years). Seizure disorder was common in our cohort of patients (23/26). Four patients had normal serum ammonia levels; the median serum concentration was 101 μ mol/L (range: 37–190 μ mol/L). Hypoglycemic symptoms could be triggered by fasting or protein meals in all patients while blood glucose could be well controlled in all patients with diazoxide. Dosage of diazoxide could be reduced by protein restriction. Attempts to lower ammonia levels failed with different therapies such as protein restriction, benzoate, or N-carbamoyl glutamate. In follow-up, 15 of 26 patients had normal intelligence. Eleven patients developed epilepsy at the age of 6 months to 11 years. De novo mutations in GLUD1 were found in 24 cases, and dominant inheritance was observed in the other two; all were heterozygous. A total of 35% (9/26) patients carried c.1493C>T (p.S445L) mutation. Conclusions . Phenotypic heterogeneity of GDH-HI patients was observed within the Chinese cohort in the present study. The fact that most patients had a GLUD1 p. S445L mutation implies that this site could be a hotspot in Chinese patients. A high frequency of GDH-HI with normal ammonia has been reported in this study. Hence, GLUD1 mutational analysis may be an important method to differential diagnosis of GDH-HI from other diazoxide-responsive CHI in Chinese patients.